Chronic Active Epstein-Barr Virus Infection With Systemic Vasculitis and Pulmonary Arterial Hypertension in a Child - Ba, Hongjun; Xu, Lingling; Peng, Huimin; Lin, Yuese; Li, Xuandi; Wang, Huishen; Qin, Youzhen (Frontiers in Pediatrics, 2019)
Introduction: A chronic active Epstein–Barr virus (EBV) infection (CAEBV), which is characterized by persistent “infectious mononucleosis-like” symptoms, can lead to cardiovascular complications, including coronary artery aneurysms. No published studies have reported an occurrence of chronic EB virus infection in conjunction with systemic vasculitis and pulmonary hypertension. Case Presentation: Herein, we present a case of a 9-year-old boy with CAEBV, associated with pulmonary arterial hypertension (PAH) and systemic vasculitis. Recurrent skin ulcers were a major early clinical manifestation in this case. The histopathological examination of a dermal biopsy sample from the lesions revealed vasculitis, and the in-situ hybridization test was positive for EBV-encoded small RNA. Results: The patient was administered immunosuppressants (prednisolone and cyclophosphamide) and targeted drugs (sildenafil and bosentan) to control the pulmonary pressure. This combination therapy decreased the systolic pulmonary arterial pressure to 40 mm Hg (on echocardiography), and the N-terminal pro b-type natriuretic peptide level also reduced to 62.3 pg/ml. After discontinuation of prednisone, the child developed shortness of breath, edema, and oliguria. He was again started on prednisone, with an addition of thalidomide. Sildenafil was replaced by riociguat, due to the side effect of penile erection. The patient is being followed up every 2 months at the clinic. The most recent follow-up visit was 2 weeks before this report was written, during which, the child was observed to have no rash, shortness of breath, edema, and other symptoms. Written informed consent was obtained from the parents for the publication of this case report. Conclusion: A CAEBV should be considered among the differential diagnoses while managing a pediatric patient with secondary PAH and systemic vasculitis. However, elucidation of its potential pathophysiological mechanisms requires further study.